Exploration of Community Structure and Density of Sea Cucumbers (Holothuroidea) in the Tropical Waters of Abang Island, Batam - Yulia Savitri; Yarsi Efendi; Fauziah Syamsi (Universitas Labuhanbatu, 2025)
Background: Coral reef ecosystems in tropical waters are highly productive and biodiverse, with sea cucumbers (Holothuroidea) serving essential ecological functions as detritivores, contributing to nutrient cycling, sediment bioturbation, and substrate quality. Despite their ecological and economic significance, data on the community structure and density of sea cucumbers in Abang Island remain scarce. This study aimed to assess the species composition, density, and ecological patterns of Holothuroidea in the tropical waters of Abang Island, Batam. Methodology: Field surveys were conducted using a transect-quadrat method, with environmental parameters (temperature, salinity, pH, dissolved oxygen) measured in situ. Findings: Five species were recorded: Holothuria leucospilota, H. atra, H. scabra, H. fuscocinerea, and H. pardalis. Species composition was dominated by H. leucospilota at Station 1 and H. fuscocinerea at Station 2. The highest density was 0.130 ind/m² for H. leucospilota at Station 1, and 0.150 ind/m² for H. fuscocinerea at Station 2. Community analysis showed greater diversity at Station 1 (H′ = 1.07) but higher dominance at Station 2 (D = 0.691). Pearson correlation indicated that salinity and temperature were the most influential factors affecting abundance, varying by habitat type. These results suggest that habitat characteristics, particularly substrate and vegetation, shape species distribution in small island ecosystems. Contribution: This study provides the first baseline data on sea cucumbers in Abang Island, offering novel insights into the linkage between environmental parameters and species-specific distribution patterns, and supporting conservation and sustainable management of these ecologically and economically valuable resources